(untitled) (Bangladesh Journal of Botany, 2014)
Ten diverse tossa jute genotypes of different eco-geographic origin were crossed with four well adapted varieties as testers to produce 40 F1s in line × tester mating design. Based on general and specific combining ability, 10 desirable cross combinations were selected and carried forward up to F4 generation by modified bulk method for further selection. Out of 890 selected promising single plant progenies from different cross combinations at F5 generation, 223 were further selected for premature flowering resistance and better growth performance over the ruling checks by sowing them at middle of March. Among 223 promising lines, 13 were short listed based on fibre yield and fibre quality parameters. Yield performance of these elite lines evinced that six lines viz. JRO 2405, JRO 2402, JRO 2404, JRO 2602, JRO 2406 and JRO 2407 were critically different from both the check varieties, JRO 524 and JRO 8432. These six high yielding lines having comparable or better fibre quality and showing resistance to premature flowering enabled them to be most suitable to fit in multiple cropping systems. Out of these 6 elite lines, JRO 2407 was identified as a new variety of tossa jute. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19740 Bangladesh J. Bot. 43(1): 9-17, 2014 (June)